Peran Madrasah Diniyah Fathul Ulum dalam Menanamkan Karakter Religius Pada Anak - Wahid Burhanuddin; Nafi'ah Nafi'ah (Social Science Academic, 2025)
The role of madrasah diniyah is to cultivate character by getting used to students reading yasin together, as well as getting used to praying Asr in congregation before all students go home. The reading of the yasin letter is routinely carried out at Madrasah Diniyah Fathul Ulum every day before the learning takes place. The role of madrasah diniyah Fathul ulum in instilling children's religious character is that in madrassas are always suppressed by worship practices ranging from purification to other worship. When students are in the madrasah all these things are instilled through habituation, also instilled other characters, for example help help, love of almsgiving, and other characters Strategies for cultivating religious character at Madrasah Diniyah Fathul ulum include by getting used to students reading the Qur'an, as well as the habit of praying Asr in congregation followed by dhikr together before all students go home, as well as the habit of upholding manners to the ustadz and ustadzah so that become accustomed to respect older people.